Intrinsic piezoelectric antibacterial polylactic acid aerogel fiber and preparation method thereof
Patent Information
- Application Number
- CN202611379892.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
然而利用共混复合、喷涂、表面负载抗菌剂等方式将抗菌剂引入医疗织物的方法,存在抗抑菌性能持续时间较短、耐洗涤性较差、及抗菌剂自身的毒性及脱落失效对人体和环境带来危害等问题
外加电场被证实可有效破坏细菌/病毒静电稳定性,使其细胞膜去极化,并通过触发水分子微电解、产生活性氧种而表现出特异性抗菌效果;聚乳酸纤维内部长链大分子沿纤维轴向规整排列,呈现出显著的各向异性分子堆砌结构,表现出压电抗菌活性。本发明采用多官能扩链支化剂,通过两步反应性加工方法构筑以PEG链段为核心链节、PDLA链段为末端嵌段的多臂支化PDLA-b-PEG嵌段聚合物,将其引入PLLA基体进行共混复合,其多臂结构的强端基效应及柔性PEG嵌段对链段运动的促进作用,可显著增强PDLA嵌段的运动能力,加速其向PLLA对映体的分子扩散,从而促使体系在熔融纺丝快速冷却阶段高效构筑立构复合物(SC)结晶,由SC晶所构成的物理缠结网络结构,有利于克服PLLA纺丝体系熔体弱黏弹性,改善其可纺性及可拉伸性,提升纤维分子取向程度,同时,SC晶的形成可使PLA链构象有序化程度提高、C=O偶极子平行排布增强,而柔性PEG链节的引入可提高聚乳酸体系柔韧性及变形能力,从而大幅提升聚乳酸体系压电活性。
Abstract
Description
Technical Field
[0001] This invention relates to an intrinsic piezoelectric antibacterial polylactic acid aerogel fiber and its preparation method, belonging to the field of polymer preparation and processing. Background Technology
[0002] In recent years, there has been an urgent need for medical textiles such as protective masks, protective clothing, and patient bedding with antibacterial properties. Polylactic acid (PLA) has excellent biocompatibility and biodegradability, and is non-toxic and non-irritating. PLA fiber is known as "green fiber" or "corn fiber" because it has high mechanical strength, is skin-friendly, and non-allergenic. It also has a certain natural anti-mite and antibacterial function due to its slightly acidic nature. Rong Chengbao, Sun Hui, et al., Journal of Textile Research, 2024, 45(1): 48-55, mixed Ag-Cu NPs nano-alloys with PLA spinning solution and prepared PLA / Ag-Cu NPs composite nanofiber membranes with different compositions by electrospinning technology. When the Ag-Cu NPs content was 7wt%, the antibacterial rate of the composite nanofiber membrane against Staphylococcus aureus and Escherichia coli reached 99%. Chen Huanhuan, Chen Kaikai, et al., Journal of Textile Research, 2023, 44(2): 34-43, mixed PLA with the natural antibacterial agent thymol and prepared PLA antibacterial fibers by melt spinning. When the mass fraction of thymol was greater than 15%, the antibacterial rate of PLA antibacterial fibers reached more than 99.99%, which could completely inhibit the growth of Staphylococcus aureus and Escherichia coli. However, methods of introducing antibacterial agents into medical fabrics through blending, spraying, or surface loading have problems such as short duration of antibacterial properties, poor washability, and the toxicity of the antibacterial agents themselves and the harm to human health and the environment caused by their detachment and failure.
[0003] Barium titanate, potassium sodium niobate, and other piezoelectric ceramics, as well as polyvinylidene fluoride (PVDF) piezoelectric films, possess specific antibacterial effects through the electric field generated by the piezoelectric effect. However, neither of these can be directly used as green and environmentally friendly medical fabrics. PLA fibers, on the other hand, exhibit a highly anisotropic molecular stacking structure with long-chain macromolecules arranged regularly along the fiber axis, demonstrating piezoelectric activity. Therefore, when PLA is spun into fibers for use in medical fabrics, it is expected to convert the biomechanical energy generated by dynamic external forces such as human movement into electrical energy during use, thereby forming a micro-electric field within the fabric. This would allow for intrinsic antibacterial function without the addition of any antibacterial agents. However, related research reports are relatively scarce. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies by providing an intrinsically piezoelectric antibacterial polylactic acid aerogel fiber and its preparation method. Its key feature is that it utilizes polylactic acid, which has excellent biocompatibility, is renewable, and is fully biodegradable. A multifunctional chain extender is employed, and a two-step reactive processing method is used to construct a multi-arm branched PDLA-b-PEG block polymer with polyethylene glycol (PEG) segments as core segments and polydextral lactic acid (PDLA) segments as end blocks. This polymer is then blended with polylactic acid (PLLA). The strong end-group effect of the multi-arm structure and the promoting effect of the flexible PEG blocks on chain segment movement significantly enhance the mobility of the PDLA blocks, accelerating their molecular diffusion towards PLLA enantiomers and constructing abundant stereocomposite crystals, thereby improving its viscoelasticity and spinnability. The degree of crystallinity and orientation of polylactic acid (PLLA) is improved, and the parallel arrangement of C=O dipoles is enhanced. The introduction of flexible PEG segments can improve the flexibility and deformability of the polylactic acid system, thereby obtaining a PLLA / PDLA-b-PEG blend spinning system with high piezoelectric activity. Further, a composite solvent with a suitable good solvent / bad solvent mass ratio is selected to prepare a solution of PLLA / PDLA-b-PEG blend with a certain concentration. The blend is then spun using an electrospinning process, and the spinning process parameters are controlled. After drying to remove residual solvent, PLLA / PDLA-b-PEG aerogel fibers are obtained using the principle of non-solvent-induced phase separation. The formation of its hierarchical porous structure is conducive to further improving the deformability and piezoelectric activity of polylactic acid fibers, thereby endowing polylactic acid fibers with excellent intrinsic piezoelectric antibacterial function.
[0005] The objective of this invention is achieved by the following technical measures, wherein the raw material fractions are all by weight unless otherwise specified.
[0006] A method for preparing intrinsically piezoelectric antibacterial polylactic acid aerogel fiber includes the following steps: Preparation of PLLA / PDLA-b-PEG blend spinning system Mix 20-100 parts of polyethylene glycol (PEG) with 0.5-5 parts of antioxidant evenly, and add the mixture to a HAKKE internal mixer for melt mixing at a speed of 10-200 rpm and a chamber temperature of 170-200℃. Then add 0.05-1 parts of chain extender / brancher and react for 3-30 minutes. Next, add 100 parts of polydextral lactic acid (PDLA) to the mixing chamber for melt blending, and then add 0.1-3 parts of chain extender / brancher and react for 3-3 minutes. Within 0 minutes, a chain-extended branched PDLA-b-PEG copolymer was obtained; 100 parts of poly-L-lactic acid were further mixed with 10-100 parts of PDLA-b-PEG block polymer and 0.05-5 parts of antioxidant, and the mixture was melt-blended, granulated and dried using a twin-screw extruder at a screw speed of 100-200 rpm and a barrel temperature of 150-220℃ to obtain a PLLA / PDLA-g-PEG blend spinning system; The weight-average molecular weights of the PLLA and PDLA are 1×10⁻⁶. 4 ~8×10 5 The weight-average molecular weight of PEO is 2 × 10⁻⁶. 3 ~5×10 5 The chain extender / branching agent is any one of pentaerythritol glycidyl ether, pyromellitic dianhydride, triphenylmethane triisocyanate, and lysine triisocyanate; the antioxidant is any one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester (i.e., Irganox 1010), N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexamethylenediamine (i.e., Irganox 1098), β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate octadecyl ester (i.e., Irganox 1076), triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylbenzyl)propionate (i.e., Irganox 245), and 2,6-di-tert-butyl-4-methylphenol (i.e., BHT(264)). Preparation of PLLA / PDLA-b-PEG intrinsic piezoelectric antibacterial aerogel fibers The PLLA / PDLA-g-PEG blend spinning system was dissolved in a mixed solvent composed of a good solvent and a bad solvent in a certain mass ratio to obtain a PLLA / PDLA-g-PEG spinning solution with a concentration of 5-20 wt%. The solution was then transferred to a spinning injector for spinning. The spinning voltage was 10-25 kV, the drum speed was 100-2000 rpm, the drum temperature was 25-45℃, and the spinning rate was 0.1-15 mL / h. After spinning, the resulting fiber membrane was dried at 40℃-60℃ for 12-72 h to obtain PLLA / PDLA-b-PEG intrinsic piezoelectric antibacterial aerogel fiber.
[0007] The good solvent is any one of dichloromethane, trichloromethane, hexafluoroisopropanol, 1,2-dichloroethane, ethyl acetate, tetrahydrofuran, and acetone; the bad solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethane, cyclohexane, methanol, and ethanol; the mass ratio of the good solvent to the bad solvent is any one of 9 / 1, 8 / 2, 7 / 3, 6 / 4, and 5 / 5.
[0008] The present invention has the following advantages: This invention addresses the urgent need for medical fabrics with antibacterial properties by aiming to prepare an intrinsically piezoelectric antibacterial polylactic acid aerogel fiber, which has the following advantages: An applied electric field has been shown to effectively disrupt the electrostatic stability of bacteria / viruses, depolarizing their cell membranes and exhibiting specific antibacterial effects by triggering micro-electrolysis of water molecules and generating reactive oxygen species. The long-chain macromolecules inside polylactic acid fibers are regularly arranged along the fiber axis, exhibiting a significant anisotropic molecular stacking structure and demonstrating piezoelectric antibacterial activity. This invention employs a multifunctional chain extender and branching agent to construct a multi-arm branched PDLA-b-PEG block polymer with PEG segments as core segments and PDLA segments as terminal blocks through a two-step reactive processing method. This polymer is then introduced into a PLLA matrix for blending. The strong end-group effect of its multi-arm structure and the promoting effect of flexible PEG segments on chain segment movement can significantly enhance the mobility of PDLA segments and accelerate their molecular diffusion to PLLA enantiomers. This promotes the efficient construction of stereocomplex (SC) crystallization during the rapid cooling stage of melt spinning. The physical entanglement network structure formed by SC crystals helps overcome the weak viscoelasticity of the PLLA spinning system melt, improves its spinnability and stretchability, and enhances the degree of fiber molecular orientation. At the same time, the formation of SC crystals can improve the conformational order of PLA chains and enhance the parallel arrangement of C=O dipoles. The introduction of flexible PEG segments can improve the flexibility and deformability of the polylactic acid system, thereby significantly improving the piezoelectric activity of the polylactic acid system.
[0009] By further selecting a composite solvent with a suitable good solvent / bad solvent mass ratio, the PLLA / PDLA-b-PEG blend was prepared into a solution of a certain concentration. The blend was then spun using an electrospinning process. PLLA / PDLA-b-PEG porous aerogel fibers were obtained by utilizing the principle of non-solvent-induced phase separation. The formation of a hierarchical porous structure composed of porous fiber membranes and porous aerogel fibers is beneficial to further improving the deformability and piezoelectric activity of polylactic acid fibers, thereby endowing them with excellent intrinsic piezoelectric antibacterial function. Detailed Implementation
[0010] The present invention will be specifically described below through embodiments. It should be noted that these embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.
[0011] Comparative Example 1 Poly-L-lactic acid (PLLA) was dissolved in hexafluoroisopropanol to obtain a 12% PLLA spinning solution. This solution was then transferred to a spinning injector for spinning. The spinning voltage was 15 kV, the roller speed was 200 rpm, the roller temperature was room temperature, and the spinning rate was 0.5 mL / h. After spinning, the resulting fiber membrane was dried at 40℃ for 10 h to obtain a PLLA nanofiber membrane with an output voltage of up to 3.58V.
[0012] Example 1 20 portions with a molecular weight of 5×10 4 Polyethylene glycol (PEG) was uniformly mixed with 0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and then melt-mixed in a HAKKE internal mixer at a speed of 30 rpm and a chamber temperature of 180°C. Subsequently, 0.5 parts of triphenylmethane triisocyanate were added, and after reacting for 10 minutes, 100 parts of a 1×10⁻⁶ molecular weight compound were added. 4 Poly(D-lactic acid) (PDLA) was melt-blended in a mixing chamber, and then 1 part of triphenylmethane triisocyanate was added and reacted for 10 minutes to obtain chain-extended branched PDLA-b-PEG copolymer; further, 100 parts of a copolymer with a molecular weight of 17×10 4 Poly(L-lactic acid) was uniformly mixed with 20 parts of PDLA-b-PEG block polymer and 0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]. The mixture was then melt-blended, granulated, and dried using a twin-screw extruder at a screw speed of 100 rpm and a barrel temperature of 150-230℃ to obtain a PLLA / PDLA-g-PEG blended spinning system. The PLLA / PDLA-g-PEG blend spinning system was dissolved in a 8 / 2 mass ratio of dichloromethane / N,N-dimethylformamide mixed solvent to obtain a 12wt% PLLA / PDLA-g-PEG spinning solution. This solution was then transferred to a spinning injector for spinning. The spinning voltage was 15 kV, the roller speed was 200 rpm, the roller temperature was 25℃, and the spinning rate was 0.5 mL / h. After spinning, the resulting fiber membrane was dried at 40℃ for 40 h to obtain PLLA / PDLA-b-PEG intrinsic piezoelectric antibacterial aerogel fiber. Its output voltage can reach 8.0V, and its antibacterial rate against Escherichia coli reaches 96%, exhibiting excellent piezoelectric antibacterial function.
[0013] Example 2 50 portions with a molecular weight of 1×10 5 Polyethylene glycol (PEG) was uniformly mixed with 0.8 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and melt-mixed in a HAKKE internal mixer at a speed of 50 rpm and a chamber temperature of 190°C. Then, 1 part of triphenylmethane triisocyanate was added, and after reacting for 15 minutes, 100 parts of a 1×10⁻⁶ molecular weight compound were added. 5 Poly(D-lactic acid) (PDLA) was melt-blended in a mixing chamber, followed by the addition of 2 parts of triphenylmethane triisocyanate and a reaction time of 20 minutes to obtain a chain-extended branched PDLA-b-PEG copolymer; further, 100 parts of a copolymer with a molecular weight of 17 × 10⁻⁶ was added... 4Poly(L-lactic acid) was uniformly mixed with 40 parts of PDLA-b-PEG block polymer and 0.8 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]. The mixture was then melt-blended, granulated, and dried using a twin-screw extruder at a screw speed of 150 rpm and a barrel temperature of 150-230℃ to obtain a PLLA / PDLA-g-PEG blend spinning system. The PLLA / PDLA-g-PEG blend spinning system was dissolved in a 7 / 3 mass ratio of hexafluoroisopropanol / dimethyl sulfoxide mixed solvent to obtain a 15wt% PLLA / PDLA-g-PEG spinning solution. This solution was then transferred to a spinning injector for spinning. The spinning voltage was 20 kV, the roller speed was 1000 rpm, the roller temperature was 30℃, and the spinning rate was 10 mL / h. After spinning, the resulting fiber membrane was dried at 50℃ for 48 h to obtain PLLA / PDLA-b-PEG intrinsic piezoelectric antibacterial aerogel fiber. Its output voltage can reach 15.0V, and its antibacterial rate against Escherichia coli reaches 98%, exhibiting excellent piezoelectric antibacterial function.
Claims
1. An intrinsically piezoelectric antibacterial polylactic acid aerogel fiber and its preparation method, characterized in that... This intrinsic piezoelectric antibacterial aerogel fiber is based on polylactic acid (PLA), which is biocompatible, renewable, and fully biodegradable. A multifunctional chain extender is used to construct a multi-arm branched PDLA-b-PEG block polymer with polyethylene glycol (PEG) segments as core segments and polydextral lactic acid (PDLA) segments as terminal blocks through a two-step reactive processing method. This PDLA-b-PEG is then blended with polylactic acid (PLLA) to construct abundant stereocomposite crystals, resulting in a high-voltage electroactive PLLA / PDLA-b-PEG blend spinning system. Further, a suitable good / bad solvent mass ratio is selected to prepare a solution of the PLLA / PDLA-b-PEG blend at a certain concentration. The blend is then electrospinned, and the spinning process parameters are controlled. After drying to remove residual solvent, the intrinsic piezoelectric antibacterial aerogel fiber of PLLA / PDLA-b-PEG is obtained using the principle of non-solvent-induced phase separation.
2. The polylactic acid intrinsically piezoelectric antibacterial aerogel fiber as described in claim 1, wherein the preparation method comprises the following steps: Preparation of PLLA / PDLA-b-PEG blend spinning system Mix 20-100 parts of polyethylene glycol (PEG) with 0.5-5 parts of antioxidant evenly, and add the mixture to a HAKKE internal mixer for melt mixing at a speed of 10-200 rpm and a chamber temperature of 170-200℃. Then add 0.05-1 parts of chain extender / brancher and react for 3-30 minutes. Next, add 100 parts of polydextral lactic acid (PDLA) to the mixing chamber for melt blending, and then add 0.1-3 parts of chain extender / brancher and react for 3-3 minutes. Within 0 minutes, a chain-extended branched PDLA-b-PEG copolymer was obtained; 100 parts of poly-L-lactic acid were further mixed with 10-100 parts of PDLA-b-PEG block polymer and 0.05-5 parts of antioxidant, and the mixture was melt-blended, granulated and dried using a twin-screw extruder at a screw speed of 100-200 rpm and a barrel temperature of 150-220℃ to obtain a PLLA / PDLA-g-PEG blend spinning system; The weight-average molecular weights of the PLLA and PDLA are 1×10⁻⁶. 4 ~8×10 5 The weight-average molecular weight of PEO is 2 × 10⁻⁶. 3 ~5×10 5 The chain extender / branching agent is any one of pentaerythritol glycidyl ether, pyromellitic dianhydride, triphenylmethane triisocyanate, and lysine triisocyanate; the antioxidant is any one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester (i.e., Irganox 1010), N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexamethylenediamine (i.e., Irganox 1098), β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate octadecyl ester (i.e., Irganox 1076), triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylbenzyl)propionate (i.e., Irganox 245), and 2,6-di-tert-butyl-4-methylphenol (i.e., BHT(264)). Preparation of PLLA / PDLA-b-PEG intrinsic piezoelectric antibacterial aerogel fibers The PLLA / PDLA-g-PEG blend spinning system was dissolved in a mixed solvent composed of a good solvent and a bad solvent in a certain mass ratio to obtain a PLLA / PDLA-g-PEG spinning solution with a concentration of 5-20 wt%. The solution was then transferred to a spinning injector for spinning. The spinning voltage was 10-25 kV, the drum speed was 100-2000 rpm, the drum temperature was 25-45℃, and the spinning rate was 0.1-15 mL / h. After spinning, the resulting fiber membrane was dried at 40℃-60℃ for 12-72 h to obtain PLLA / PDLA-b-PEG intrinsic piezoelectric antibacterial aerogel fiber. The good solvent is any one of dichloromethane, trichloromethane, hexafluoroisopropanol, 1,2-dichloroethane, ethyl acetate, tetrahydrofuran, and acetone; the bad solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethane, cyclohexane, methanol, and ethanol; the mass ratio of the good solvent to the bad solvent is any one of 9 / 1, 8 / 2, 7 / 3, 6 / 4, and 5 / 5.